2012
DOI: 10.1177/183693911203700304
|View full text |Cite
|
Sign up to set email alerts
|

The transition to school of children with developmental disabilities: Views of parents and teachers

Abstract: THE TRANSITION FROM EARLY INTERvENTION programs to inclusive school settings presents a range of social challenges for children with developmental disabilities. In Queensland, in the year of transition to school, many children with developmental disabilities attend an Early Childhood Development Program for two to three days each week and also begin attendance in a mainstream program, with the latter increasing to full-time attendance during the year. Quantitative and qualitative data was collected by question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Measures of child outcomes are all reliable, valid scales, with excellent psychometric properties, sensitivity to intervention and widely used in Australia and internationally. Measures of possible determinants also have robust psychometric properties, are brief, and are mostly drawn from the Longitudinal Study of Australian Children (LSAC) [41,42]. Family demographic information collected at baseline (and repeated for those variables that can change over time) include parents’ age, employment, education, mental health diagnoses (including family history of ADHD), income, family composition and whether the child has ever lived for an extended period of time out of parental care.…”
Section: Methodsmentioning
confidence: 99%
“…Measures of child outcomes are all reliable, valid scales, with excellent psychometric properties, sensitivity to intervention and widely used in Australia and internationally. Measures of possible determinants also have robust psychometric properties, are brief, and are mostly drawn from the Longitudinal Study of Australian Children (LSAC) [41,42]. Family demographic information collected at baseline (and repeated for those variables that can change over time) include parents’ age, employment, education, mental health diagnoses (including family history of ADHD), income, family composition and whether the child has ever lived for an extended period of time out of parental care.…”
Section: Methodsmentioning
confidence: 99%
“…Effective collaboration is the practice that supports mutuality. A number of studies have drawn conclusions consistent with this approach (Darragh, 2009;Drew, DeBortoli, Brentnall & Bundy, 2014;Espe-Sherwindt, 2008;Walker et al, 2012). Indeed, development of positive working relationships with families is an essential attribute and skill required by both early childhood educators and ECI professionals (ECIA, 2016).…”
Section: Positive Relationship-building Practicesmentioning
confidence: 99%
“…ECI professionals act as a 'resource', providing specialist expertise, knowledge and skills to families as they evaluate and select their choices (Bourke-Taylor et al, 2015). As school transition projects in New South Wales (NSW) have found, resources and information provided by ECI professionals assisted families to identify goals and supports for their child (NSW Government, 2015;Walker et al, 2012). Furthermore, feedback about ECI professionals in Victoria has consistently found that families valued the information provided, as well as opportunities for discussion to identify the supports they considered necessary (Brien, 2014a).…”
Section: Specialist Expertise and Knowledge To Support Informed Decismentioning
confidence: 99%
“…If intervention approaches play a role, this role should not be underestimated. Thus, given that the transition to school and community is often di cult and stressful for individuals with ASD and their families, there is a pressing need for systematic knowledge of the outcomes in midchildhood and adolescence and their predictive factors in children with ASD who have been exposed to a CTM to provide timely support [23].…”
Section: Introductionmentioning
confidence: 99%